Modelling impacts of forest bioenergy use on ecosystem sustainability: Lammi LTER region, southern Finland. (June 2016) - Forsius, Martin; Akujärvi, Anu; Mattsson, Tuija; Holmberg, Maria; Punttila, Pekka; Posch, Maximilian; Liski, Jari; Repo, Anna; Virkkala, Raimo; Vihervaara, Petteri
Highlights: We have modelled impacts of forest bioenergy use on ecosystem sustainability. Impacts of management options on sustainability indicators can be evaluated. Trade-off situations were observed between bioenergy use and environmental impacts. The developed model system allows seeking for optimised solutions. Abstract: Increasing the use of forest biomass for energy production is an important mitigation strategy against climate change. Sustainable use of natural resources requires that these policies are evaluated, planned and implemented, taking into account the boundary conditions of the ecological systems affected. This paper describes the development and application of a quantitative modelling framework for evaluating integrated impacts of forest biomass removal scenarios on four key environmental sustainability/ecosystem service indicators: (i) carbon sequestration and balance, (ii) soil nutrient balances (base cations and nitrogen), (iii) nutrient leaching to surface waters (nitrogen and phosphorus), and (iv) dead wood biomass (used as proxy indicator for impacts on species diversity). The system is based on the use of spatial data sets, mass balance calculations, loading coefficients and dynamic modelling. The approach is demonstrated using data from an intensively studied region (Hämeenlinna municipality) encompassing the Lammi LTER (Long-Term Ecosystem Research) site in southern Finland. Forest biomass removal scenarios were derived from a management-oriented large-scale forestry model (MELA) based on sample plot and stand-level data from national forest inventories. These scenarios have been developed to guide future Finnish forest management with respect to bioenergy use. Using harvest residues for district heat production reduced fossil carbon emissions but also the carbon sink of forests in the case study area. Calculations of the net removal of base cations of the different scenarios ranged between −36 to −43 meq m −2  a −1, indicating that the supply of base cations (soil weathering + deposition) would be enough to sustain also energy-wood harvesting. Greatly increased nutrient removal values and increasing nitrogen limitation problems were however predicted. Clear-cuttings and site preparation were predicted to increase the load of total nitrogen (4.0%) and total phosphorus (4.5%) to surface waters, compared with background leaching. The amount of dead wood has been identified as a key factor for forest species diversity in Finland. A scenario maximising harvest residues used for bioenergy production, would decrease stem dead wood biomass by about 40%, compared with a business-as-usual scenario. Clear trade-off situations could be observed in the case study area between maximising the use of energy-wood and minimising impacts on species diversity, soil carbon and nutrient stores, and nutrient leaching. The developed model system allows seeking for optimised solutions with respect to different management options and sustainability considerations.